2015
DOI: 10.1002/mop.29513
|View full text |Cite
|
Sign up to set email alerts
|

Microwave noise parameter modeling of a GaAs HEMT under optical illumination

Abstract: This article presents the experimental results of the modeling of noise parameters for a GaAs HEMT under light exposure. The noise model is based on the equivalent-circuit representation expanded by assigning an equivalent noise temperature to each resistor. To take into account for the significant increase of the gate current under light exposure, two resistances with the associated noise temperatures have been added at the input and feedback of the intrinsic section of the circuit. The validity of the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The DC characterization showed that, under light exposure, a current increase occurred for all devices due to the threshold voltage shift related with the photovoltaic effect (illuminated current I DS = 15, 27, and 40 mA, respectively) . Furthermore, both DC and RF transconductance g m increased with illumination as well .…”
Section: Device Measurementsmentioning
confidence: 95%
“…The DC characterization showed that, under light exposure, a current increase occurred for all devices due to the threshold voltage shift related with the photovoltaic effect (illuminated current I DS = 15, 27, and 40 mA, respectively) . Furthermore, both DC and RF transconductance g m increased with illumination as well .…”
Section: Device Measurementsmentioning
confidence: 95%
“…The resulting models are shown in Figure 3 As already pointed out, one of the purposes of the present work was to verify the applicability of the proposed methodology to properly represent the noisy behavior of a HEMT device under laser excitation. To this respect, few references can be found in the literature [23][24][25][26]: Reasonably, under laser illumination, generation and recombination phenomena might arise in the gate-source and gate-drain regions, thus originating two additional noise sources located in parallel to the relevant junctions. Those noise sources affect the noise parameters in a way that they do not satisfy the DC physical constraints as is usual for a well-behaving high-frequency HEMT or MESFET device (in the frequency and temperature ranges in which 1/f noise and quantum effects can be neglected).…”
Section: Measurement System and Experimental Resultsmentioning
confidence: 99%
“…Noise behavior of devices subjected to illumination is a topic that has not yet been investigated extensively [23][24][25][26]. As a consequence, applying conventional noise modeling techniques, that is, based on the concept of equivalent temperatures [33][34][35], has been postponed to a future work, whereas a general, black-box model was adopted to extract and represent device noise parameters.…”
Section: Modeling Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…To contribute to the advancement of this semiconductor technology, many studies have been developed over the years to experimentally characterize the microwave linear performance of GaAs HEMTs and pHEMTs in terms of scattering (S-) and noise (N-) parameter measurements and to reproduce the measured behavior with equivalent-circuit based models. [8][9][10][11][12][13][14][15][16][17][18] This study is focused on the characterization and modeling of advanced on-wafer GaAs pHEMTs at microwave frequencies. To investigate the scaling of the performance of the studied transistor technology, four interdigitated devices with different number of gate fingers are analyzed.…”
Section: Introductionmentioning
confidence: 99%